The Intellectual Role of Islamizing Librarianship - Rashid Siddiqui (International Institute of Islamic Thought, 1988)
Mawlana Mawdudi (may Allah be pleased with him) has made a very thought-provoking remark in his introduction to “Al Jihad fd Islam7 He writes: “It is a natural weakness of human beings. If one is defeated in a battlefield he is also overwhelmed in the field of knowledge. He cannot contest in penmanship with one by whose sword he has been defeated.”l The inferiority of Muslims in the intellectual domain is well documented and does not need any elaboration. Now it is the task of Muslim scholars to take up the challenge of redressing the imbalance. One area of scholarship often neglected by scholars is library science. The task required to Islamize science calls for immense intellectual capacity. One should be expert not only in the field of library science but should also possess deep insight into the faith of Islam, its culture, and civilization. It is only through the combination of these qualities that a new creative discipline can be produced. Library science, as developed in the West, is bound to reflect the image of Western civilization. Subject classification, the rules for cataloguing, lists of subject headings and other techniques employed to exploit literature all portray the Western way of life. Islam has its own world view of human affairs and Islamic literature naturally will reflect this world view. To restrict Islam under the heading “religion” following the Western conceptualization violates the very basic concepts of Islamic principles. The response of librarians when faced with this challenge is to adapt the existing classification. Though such adaptations may be useful they not only hopelessly fail to tackle the real problem, but distort and disfigure the serene harmony of Islamic values. What is needed is totally new and radical approach by Muslim librarians to work out a new ...